Desperation road [videorecording (Blu-Ray + DVD)] - Smith, Michael F. (Michael Farris), 1970-; Hedlund, Garrett, 1985-; Gibson, Mel; Fitzgerald, Willa; Hurst, Ryan, 1976-; Smith, Michael F. (Michael Farris), 1970- (Lionsgate, 2023)
In a small Mississippi town, justice and the law are two very different things. A modern noir-thriller based on the acclaimed novel by Michael Farris Smith. Two lost souls, tortured by the mistakes of their past, are bound by a secret that keeps them running.